Clinical Significance of Detection of Human Papilloma Virus DNA and E6/E7 mRNA for Cervical Cancer Patients - Yu, Tingting; Wang, Chunyan (Cellular and Molecular Biology, 2022)
This study aimed to explore the clinical significance of detection of human papillomavirus (HPV) DNA and E6/E7 mRNA for cervical cancer patients. For this purpose, a total of 300 patients with cervical lesions who performed the colposcopy examination for the cervix between January 2018 and January 2020 were divided into three groups according to the level of cervical intraepithelial neoplasia (CIN): Low-level group (Group A, n = 101), high-level group (Group B, n = 149), cervical cancer group (Group C, n = 50) and gynecological inflammation group (Group D, n = 60). Tissue samples were collected from subjects above to perform the immunohistochemistry for E6/E7 protein and detection of HPV DNA and HPV E6/E7 mRNA. The results showed that HPV DNA copies and the positive rates of protein, DNA and mRNA of HPV E6/E7 in Groups A, B and C were significantly higher than those in Group D (all P<0.05), while no significant difference was identified in the comparison of the positive rate and copies of DNA among Group A, B and C (P> 0.05); in the Group A, B and C, patients had a higher positive rate of E6/E7 mRNA than those in the Group D (P<0.05), while in the Group B and C, the positive rate and copies of mRNA of HPV E6/E7 and HPV E6/E7 proteins were all higher than those in the Group A (P<0.05). In addition, the specificity of HPV E6/E7 mRNA was inferior to HPV DNA in the detection of the low-level intraepithelial neoplasia, but it performed better in the detection of the high-level intraepithelial neoplasia and cervical cancer. In general, HPV E6/E7 mRNA shows promising value in the detection of the development and progression of cervical cancer.